Sistema de autenticação para aplicativos de gestão empresarial utilizando Azure Ative Directory - Silva, João Pedro Martins da (2025)
This study addresses the development of an authentication system for business management applications, based on the use of Azure Active Directory (Azure AD). The choice of this theme is justified by the growing demand for robust information security solutions, essential for protecting sensitive data and mitigating unauthorized access in corporate environments. The main objective was to implement a solution that combines high security and ease of use, employing contemporary methodologies such as multifactor authentication (MFA) and widely used protocols, such as OAuth 2.0 and OpenID Connect. The adopted methodology included a bibliographic review, a thorough analysis of security requirements, implementation of APIs for authentication, and testing in real-world scenarios. The results indicated that the developed system demonstrated efficiency in protecting sensitive information, showed high scalability, and proved its ability to integrate with various business platforms. It is concluded that the application of technologies such as Azure AD, combined with modern authentication practices, significantly contributes to strengthening the security of corporate systems, constituting a practical and .reliable solution for the business environment.